Enhancing the development of technology and partnership-based business incubator models in indonesia: the role of human resource availability, industry connections, and access to finance - Rukmana, Arief Yanto; Barliana, Mokhamad Syaom; Widiaty, Isma; Hamdani, HR. Aam; Abdullah, Ade Gafar; Harnani, Nining; Meltareza, Ridma; Harto, Budi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to analyze the development of technology and partnership-based business incubator models in Indonesia is the subject of this study, which focuses on the importance of relationships with industry, the availability of funds, and the availability of human resources. Using a quantitative approach, with a random sampling technique of 300 samples representing start-ups and business incubators in various industries and regions in Indonesia, the study was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) 4. The findings show a strong correlation between human resource availability and technological advancement, industry ties and partnership-based business models, and startup growth and financing availability. These results highlight how innovation and entrepreneurial success in the Indonesian ecosystem can be encouraged by investing in human capital, fostering collaboration among industry stakeholders, and building a climate that supports startup financing.